Dark energy parametrizations and their effect on dark halos - Liberato, Lamartine; Rosenfeld, Rogério [UNESP] (Iop Publishing Ltd, 2006)
There are a plethora of dark energy parametrizations that can fit current supernovae Ia data. However, these data are only sensitive to redshifts up to order one. In fact, many of these parametrizations break down at higher redshifts. In this paper we study the effect of dark energy models on the formation of dark halos. We select a couple of dark energy parametrizations which are sensible at high redshifts and compute their effect on the evolution of density perturbations in the linear and non-linear regimes. Using the Press-Schechter formalism we show that they produce distinguishable signatures in the number counts of dark halos. Therefore, future observations of galaxy clusters can provide complementary constraints on the behaviour of dark energy.
Keywords: dark energy theory; cosmological perturbation theory; classical tests of cosmology; semi-analytic modelling